2018
DOI: 10.1186/s12909-018-1353-5
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of medical students to be examined in a physical examination course

Abstract: BackgroundPhysical examination courses are an essential part of the education of medical students. The aim of this study was to ascertain the factors influencing students’ motivation and willingness to participate in a physical examination course.MethodsStudents were asked to complete a questionnaire subdivided into five domains: anthropometric data, religiousness, motivation to take part in physical examination courses, willingness to be physically examined at 11 different body regions by peers or a professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…It was expected that the students would be less comfortable with the intimate areas which were proven by our results; the groin area is the most unacceptable area to be examined among both males and females, followed by the breast. That agrees with the findings of [ 7 , 11 ]. In contrast, the non- intimate areas were highly accepted to be examined by both genders which is similar to the findings of similar studies in western societies [ 3 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was expected that the students would be less comfortable with the intimate areas which were proven by our results; the groin area is the most unacceptable area to be examined among both males and females, followed by the breast. That agrees with the findings of [ 7 , 11 ]. In contrast, the non- intimate areas were highly accepted to be examined by both genders which is similar to the findings of similar studies in western societies [ 3 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…1 ) showed a big difference between the willingness of the two genders to take part in the PPE; males were more willing to participate than females, which is considered to be an interesting result that points out many underlying reasons. Religion is probably the most controversial one as other studies found [ 11 , 12 ], especially by the fact that the Syrian community is considered to be conservative, which limits the usage of PPE due to the possible interaction between the opposite genders which is forbidden in the Islamic faith. Even though the religious constraints affected both genders, our results indicated that females’ opinions were more related to religion than males’ opinions.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 142 medical students found that students acknowledged the importance of learning and practicing the physical exam but had varying levels of willingness to be examined by peers or preceptors. 42 Thirty-nine percent of female students felt unwilling to have their hip joint examined by a male peer, and 23% of female students felt unwilling to have male students examine their abdomen. 42 For more sensitive exams (e.g., groin, breast), depending on the gender of student and examiner, as many as 93% of students were unwilling to be examined by a peer.…”
Section: Trauma-informed Educational Contextmentioning
confidence: 99%
“…42 Thirty-nine percent of female students felt unwilling to have their hip joint examined by a male peer, and 23% of female students felt unwilling to have male students examine their abdomen. 42 For more sensitive exams (e.g., groin, breast), depending on the gender of student and examiner, as many as 93% of students were unwilling to be examined by a peer. 42 Students preferred self-assembled peer exam groups over same- and mixed-gender groups, suggesting that students were more comfortable when able to form their own learning cohorts.…”
Section: Trauma-informed Educational Contextmentioning
confidence: 99%
See 1 more Smart Citation